12ax-y+2ay-6x=

Simple and best practice solution for 12ax-y+2ay-6x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12ax-y+2ay-6x= equation:


Simplifying
12ax + -1y + 2ay + -6x = 0

Reorder the terms:
12ax + 2ay + -6x + -1y = 0

Solving
12ax + 2ay + -6x + -1y = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6x' to each side of the equation.
12ax + 2ay + -6x + 6x + -1y = 0 + 6x

Combine like terms: -6x + 6x = 0
12ax + 2ay + 0 + -1y = 0 + 6x
12ax + 2ay + -1y = 0 + 6x
Remove the zero:
12ax + 2ay + -1y = 6x

Add 'y' to each side of the equation.
12ax + 2ay + -1y + y = 6x + y

Combine like terms: -1y + y = 0
12ax + 2ay + 0 = 6x + y
12ax + 2ay = 6x + y

Reorder the terms:
12ax + 2ay + -6x + -1y = 6x + -6x + y + -1y

Combine like terms: 6x + -6x = 0
12ax + 2ay + -6x + -1y = 0 + y + -1y
12ax + 2ay + -6x + -1y = y + -1y

Combine like terms: y + -1y = 0
12ax + 2ay + -6x + -1y = 0

The solution to this equation could not be determined.

See similar equations:

| -8(2a+5)-4= | | 13.7+-0.1+-2.4= | | -3(-5p+8)-p= | | 2+7y=11-y-y | | 5x(5x+2)-(5x+2)= | | 6x-1=3x-43 | | 2(1-2y)+5y=3 | | 9y-2y+8=4y+38 | | 200-7x=95 | | 3025=x^2+.5625x^2 | | 5k-8=13-2k | | 2?5=-z?45 | | 10w-4w-w+2+w+9= | | 9x-(7x+6)=6 | | 2(3x-4)-10=5(x+4) | | (17x)^(1/2) | | 3025=x^2+1.7778x^2 | | 6=-1?2n | | f(x)=3sinx+4x-1 | | 6+(-3k)-24+13k-(-1)= | | 18y+1=67 | | 3x+8=2x+4fory | | 4x-15=-75 | | 3-3(7-8x)=0 | | 3-2(x+5)=17 | | (6s-5t)(6s+5t)= | | -9(4a+2)+4= | | y^2+1.7778y^2=3025 | | .5(2p-3)-4p= | | 5.88x= | | -4+11k-10+(-17k)+3= | | 2x=y-6 |

Equations solver categories